Development of nutrition edutainment program for expectant mothers in disaster situation in Padang - John Amos; Ridwan Setiawan; Rapitos Sidiq; Nindy Audia Nadira; Widdefrita Widdefrita; Sumihardi Sumihardi (AcTion: Aceh Nutrition Journal, 2024)
Expectant mothers are vulnerable to health risks during disasters such as disruption of clean water, exposure to inadequate environmental sanitation, and limited access to safe food. Padang is located on a volcanic plateau which is prone to disasters. This study aimed to develop expectant pregnant mothers on education-based nutritional education for expectant mothers in disaster situations in Padang. This study used a quasi-experimental design conducted in April-November 2019, with a sample of 100 expectant mothers, who were selected by random sampling and divided into four groups of treatments (PowerPoint, Android, website, and Android-website combination). Data were collected through interviews and questionnaires and analyzed using Wilcoxon and Kruskal-Wallis tests. Edutainment-based nutritional education has been developed based on the needs of expectant mothers in disaster situations. The results showed changes in knowledge in all groups (p<0,05), while changes in attitudes occurred in Groups B and C (p<0,05) and changes in practices occurred in Groups A and C (p<0,05) after the intervention. In conclusion, Treatment C had a significant impact on knowledge, attitudes, and practices.